2013
DOI: 10.1155/2013/374769
|View full text |Cite
|
Sign up to set email alerts
|

The Role of T Helper (TH)17 Cells as a Double-Edged Sword in the Interplay of Infection and Autoimmunity with a Focus on Xenobiotic-Induced Immunomodulation

Abstract: Extensive research in recent years suggests that exposure to xenobiotic stimuli plays a critical role in autoimmunity induction and severity and that the resulting response would be exacerbated in individuals with an infection-aroused immune system. In this context, heavy metals constitute a prominent category of xenobiotic substances, known to alter divergent immune cell responses in accidentally and occupationally exposed individuals, thereby increasing the susceptibility to autoimmunity and cancer, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…Also it can alter the host-pathogen interactions or increase the susceptibility to diseases (Gardner et al, 2010). Hemdan et al (2007) in vitro demonstrated differences in Hg effect on the Th1/Th2 balance after different cells stimulation. Authors stated that a low dose of Hg turns up the immune response towards Th2 type in the case of absence of infl ammatory component, but not in the case of Th1 immune response induced by bacterial antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also it can alter the host-pathogen interactions or increase the susceptibility to diseases (Gardner et al, 2010). Hemdan et al (2007) in vitro demonstrated differences in Hg effect on the Th1/Th2 balance after different cells stimulation. Authors stated that a low dose of Hg turns up the immune response towards Th2 type in the case of absence of infl ammatory component, but not in the case of Th1 immune response induced by bacterial antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of organisms to the heavy metal ions impairs hosts immunocompetence and increases susceptibility to the infections. Heavy metals also affect the cell physiology and modulate immune system responses (Valko et al, 2005;Holmes et al, 2009;Jomova & Valko, 2011;Hemdan et al, 2013;Pollard & Kono, 2013;Dvorožnáková & Jalčová, 2013). Due to high abundance of industrial heavy metals in exposed areas small mammals migrating in affected territories are suitable bioindicators of anthropogenic environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we documented that W 80 5EC NE is a potent adjuvant, inducing strong Th1 and Th17 immune responses [17]. The Th17 response, while constituting a protective arm defending the body against various infections, also functions as a double-edged sword constituting a risk factor that mediates the induction of autoimmune diseases [39]. Therefore, it is important to exclude the possibility that cell death caused by W 80 5EC NE may be involved in development of Th17 response associated with autoimmune or chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-2 and IL-17 have a pronounced role in the non-specific immune response and T cell differentiation. IL-2 is a regulatory cytokine produced by Th-1 cells that activates macrophages against intracellular antigens (26), since it mediates acute inflammation and DTH (27). IL-17 is a proinflammatory cytokine produced by Th-17, neutrophils and mast cells and is required for Th-17 development (28).…”
Section: Effect Of Tgc On Il-17 and Il-2 Release In Con A Pretreated mentioning
confidence: 99%